Characterization of early Chinese northern celadon with lead glaze from Caocun kiln within Yecheng site. (June 2018) - Yan, Lingtong; Sun, Heyang; Li, Li; Feng, Xiangqian
Abstract: Archaeologists found a number of ceramic shards dating to the Northern Dynasties (386–581 CE) in the Caocun kiln within the Yecheng site (Hebei Province, China). A small amount of samples with grey body and green glaze are considered as representative early northern celadon. In order to investigate the raw materials, firing process and product quality about them, we collected some shards with reddish and green glazes from this kiln site, and analyzed the chemical composition, firing temperature and phase composition. The data show that the raw materials used in this kiln can be divided into two categories according to the contents of calcium and iron. The green wares have the elemental characteristics of northern ceramic products, higher level of aluminum in the body compared to the southern. The results of phase composition indicated that the quality of bodies from Caocun kiln in this work is poor, which might be related to raw materials of high-alumina and relatively low firing temperature. All the samples are covered by lead glazes of different categories, which is significantly different from most of Chinese ancient celadon. Based on the results, it can be speculated that the manufacture of ceramic wares in Caocun kiln might be complicated. Highlights: Some rare early northern celadon were collected from Caocun kiln within Yecheng site and analyzed in a variety of methods. The glaze is rich in lead, different from general alkali celadon glaze. The quality of bodies was investigated based on the results of phase composition and firing temperature.